Actors and their Roles for Sustainable Forest Governance in South Eastern Ethiopia: The Case of Bale Eco-Region: Research article - Birhan, Endalkachew; Assefa, Engdawork; A. Petrova, Maria (Madda Walabu University Journal of Equity in Sciences and Sustainable Development, 2023)
This study examines the roles of various actors in sustainable forest governance in south-eastern Ethiopia, focusing on the Bale Eco-Region. The study used a descrip-tive design with qualitative methods, including in-depth interviews and focus group discussions. The findings indicate that all critical actors have the opportunity to par-ticipate in forest governance, but this has not led to desired outcomes. The govern-ment and organized forest communities have a crucial role in jointly governing the forests through participatory forest management. The government, specifically the Environment, Forest, and Climate Change Authorities, regulates and controls all for-ests, while Oromia Forest and Wildlife is responsible for protecting and managing forests in the Oromia Regional State. Non-governmental organizations (NGOs), such as FARM Africa and SOS Sahel Ethiopia, indirectly influence government decisions and implement them in the Bale Eco-Region. Research institutions and media have a limited role in influencing government decisions and implementation. Despite these efforts, deforestation and forest degradation persist, and there has been insufficient improvement in the lives of forest-dependent communities. Therefore, it is crucial to empower these actors to effectively contribute to sustainable forest governance.